Pathological ATPergic Signaling in Major Depression and Bipolar Disorder - Illes, Peter; Verkhratsky, Alexei; Tang, Yong (Frontiers in Molecular Neuroscience, 2020)
The mood disorders major depression (MD) and bipolar disorder (BD) have high lifetime prevalence in the human population and accordingly generate huge costs for health care. Efficient, rapidly acting and side-effect free pharmaceuticals are hitherto not available and therefore, the identification of new therapeutic targets is an imperative task for (pre)clinical research. Such a target may be the purinergic P2X7 receptor (R) which is located in the CNS at microglial and neuroglial cells mediating neuroinflammation. MD and BD are due to neuroinflammation caused in the first line by the release of the pro-inflammatory cytokine interleukin-1β (IL-1β) from microglia. IL-1β in turn induces the secretion of corticotropin releasing hormone (CRH) and in consequence ACTH/glucocorticoids which together with a plethora of further cytokines/chemokines leads to mood disorders. A number of biochemical/molecular biological measurements including the use of P2X7R- or IL-1β-deficient mice confirmed this chain of events. More recent studies showed that a decrease in the astrocytic release of ATP in the pre-frontal cortex and hippocampus are major causes of mood disorders. It is an attractive hypothesis that compensatory increases in P2X7Rs in these areas of the brain are the immediate actuators of MD and BD. Hence, blood-brain barrier permeable P2X7R antagonists may be promising therapeutic tools to improve depressive disorders in humans.